Divergence rates of subviral pathogens of angiosperms abruptly decreased at the Cretaceous-Paleogene boundary - Piotr Bajdek (Rethinking Ecology, 2019)
Biogeographic distribution of infected plants and the continental drift theory allow a tentative time calibration of the phylogenetic tree of Pospiviroidae. Hypothetically, viroids evolved in the late Early Cretaceous shortly after the appearance of angiosperms, which constitute their only known hosts. No decline in the estimated divergence rates of Pospiviroidae is observed during the Late Cretaceous but it appears that they abruptly decreased at the Cretaceous-Paleogene boundary. However, an adaptive radiation of Pospiviroidae which occurred in the late Paleocene may reflect a recovery from the Cretaceous-Paleogene (K–Pg) mass extinction. It seems that the evolutionary history of viroids has been in part shaped by radiation and extinction events of angiosperms. Herein, for the first time I show the probable impact of a mass extinction event on the divergence rates of subviral pathogens, which are the simplest known “lifeforms”.